Operating and sanitation characteristics of household biogas in some communes of the Ha Nam province in 2014 - Luu Quoc Toan; Hung Nguyen-Viet; Le Thi Thu; Nguyen Mai Huong; Phuc Pham Duc (2016)
Research the operation of biogas plant in 451 households in three communes of Hanam province in 2014. Field survey had interviewed farmers about the operation using household biogas plant. Biogas wastewater samples were collected in tank pressure of biogas plant to test the hygiene indicators. The study results showed that the proportion of households, that use pig manure, poultry manure and human excrement for biogas loaded were 90.2%, 29.7% and 80.3%, respectively. Biogas waste water was discharged into drains directly and commune lakes shared that were 66.5% and 12.9%, respectively. The chemical and microbiological index of wastes was reduced by biogas treatment. However, the rate of biogas sewage had detected Salmonella, Giardia, and Cryptosporidium that was from 34.7 to 56.0%. E. coli concentration in the biogas wastewater of tank pressure has exceeded the WHO recommendation that are applied for animal wastewater using in agriculture. The people have used protection when exposed to sewage of biogas plant. However, protection using are not comprehensive.